The Effect of Using Video Animation to Increase the Seventh Grader Students’ Speaking English Skill and Motivation at Islamic Junior High School - Emilizar, Emilizar; Welya, Welya; Puspitasari, Maya (STIT Ahlussunnah Bukittinggi, 2025)
This study was conducted with the aim of determining the effect of using animated videos on improving English skills and student motivation. This type of research is quantitative research with a quasi-experimental research design with one experimental class and one control class. This study was conducted by giving a test before treatment. Then, a test was conducted after the treatment using animated video media in the experiment class and using conventional techniques in the control class. The sample in this study was 23 students from grade VII.4 as the experimental class and 23 students from grade VII.5 as the control class. Data collection techniques used in this study were tests, questionnaires, and interviews. The tests were analyzed using the mean and gain comparison formulas. The results showed that there was an effect of using animated video media in English learning to improve students' speaking skills and motivation. This can be seen from the mean value in the experimental class of 82.00 and the mean value in the control class of 76.96, and student motivation was 81.50 (very high). Meanwhile, the gain comparison for the experimental class was +25.54, and the gain comparison for the control class was +17.61. It can be concluded that there is a significant influence on the use of animated video media in English learning to improve students' speaking skills and motivation.